Screening of a microbial consortium with efficient corn stover degradation ability at low temperature - Qinggeer; Ju-lin GAO; Xiao-fang YU; Bao-lin ZHANG; Zhi-gang WANG; Borjigin Naoganchaolu; Shu-ping HU; Ji-ying SUN; Min XIE; Zhen WANG (Journal of Integrative Agriculture)
To speed up the degradation of corn stover directly returned to soil at low temperature, the corn stover-degrading microbial consortium GF-20, acclimated to biological decomposition in the frigid region, was successfully constructed under a long-term limiting substrate. To evaluate its potential in accelerating the decomposition of un-pretreated corn stover, the decomposing property, fermentation dynamic and the microbial diversity were analyzed. GF-20 degraded corn stover by 32% after 15-day fermentation at 10°C. Peak activities of filter paperlyase (FPA), β-glucosidases (CB), endoglucanases (Cx), and cellobiohydrolases (C1) were 1.15, 1.67, 1.73, and 1.42 U mL−1, appearing at the 6th, 3rd, 11th, and 9th d, respectively. The pH averaged at 6.73–8.42, and the optical density (OD) value peaked at 1.87 at the 120 h of the degradation process. Cellulase, hemicellulase and lignin in corn stover were persistently degraded by 44.85, 43.85 and 25.29% at the end of incubation. Result of denaturing gradient gel electrophoresis (DGGE) profiles demonstrated that GF-20 had a stable component structure under switching the temperature and pH. The composition of the GF-20 was also analyzed by constructing bacterial 16S rDNA clone library and fungal 18SrDNA-PCR-DGGE. Twenty-two bacterial clones and four fungal bands were detected and identified dominant bacteria represented by Cellvibrio mixtus subsp., Azospira oryzae, Arcobacter defluyii, and Clostridium populeti and the fungi were mainly identified as related to Trichosporon sp.